Evolution of replicative DNA polymerases in archaea and their contributions to the eukaryotic replication machinery - Makarova, Kira S.; Krupovic, Mart; Koonin, Eugene V. (Frontiers in Microbiology, 2014)
The elaborate eukaryotic DNA replication machinery evolved from the archaeal ancestors that themselves show considerable complexity. Here we discuss the comparative genomic and phylogenetic analysis of the core replication enzymes, the DNA polymerases, in archaea and their relationships with the eukaryotic polymerases. In archaea, there are three groups of family B DNA polymerases, historically known as PolB1, PolB2 and PolB3. All three groups appear to descend from the last common ancestors of the extant archaea but their subsequent evolutionary trajectories seem to have been widely different. Although PolB3 is present in all archaea, with the exception of Thaumarchaeota, and appears to be directly involved in lagging strand replication, the evolution of this gene does not follow the archaeal phylogeny, conceivably due to multiple horizontal transfers and/or dramatic differences in evolutionary rates. In contrast, PolB1 is missing in Euryarchaeota but otherwise seems to have evolved vertically. The third archaeal group of family B polymerases, PolB2, includes primarily proteins in which the catalytic centers of the polymerase and exonuclease domains are disrupted and accordingly the enzymes appear to be inactivated. The members of the PolB2 group are scattered across archaea and might be involved in repair or regulation of replication along with inactivated members of the RadA family ATPases and an additional, uncharacterized protein that are encoded within the same predicted operon. In addition to the family B polymerases, all archaea, with the exception of the Crenarchaeota, encode enzymes of a distinct family D the origin of which is unclear. We examine multiple considerations that appear compatible with the possibility that family D polymerases are highly derived homologs of family B. The eukaryotic DNA polymerases show a highly complex relationship with their archaeal ancestors including contributions of proteins and domains from both the family B and the family D archaeal polymerases.